(untitled) (KULT_online, 2019)
The collection of articles titled Critical Human Rights, Citizenship and Democracy Education, Entanglements and Regenerations and published as a part of Bloomsburry’s series on Critical Education revisits some of the numerous engagements with the human rights project and its educational forms. The aim is to draw attention to controversies and a necessary critique of the concept of global pedagogy for human rights, democracy, and citizenship, in order to underline what many critical theorists and specifically post- and decolonial scholars have been stressing for decades: The ongoing suppression of various voices, namely those from the global south, whose perspectives on human rights might disrupt the hegemonic narrative of the global north – a narrative deeply intertwined with racism and colonial violence. Mindful of these entanglements, the authors within the volume probe into the limits of human rights as a critical endeavor and push for answers to the question of whether a critical human rights project is possible.